Analisis Pengaruh Just-In-Time terhadap efisiensi Logistik dan pengendalian inventaris di Perusahaan TOYOTA - Adawiyah, Keishya Robiatul; Takaya , Rowlan (Universitas Pahlawan Tuanku Tambusai, 2025)
Logistics is a process in which planning, implementation, and control of the flow of goods, information and resources from the main point (origin) to the end consumer to meet consumer needs efficiently and effectively. Logistics also includes various activities in it such as procurement of raw materials, management, storage, and distribution of finished products. So the main goal of logistics in operational management is to ensure a product or service reaches the customer by covering optimal costs, the right time (efficient) and must be in good condition without any damage to the product. This logistics plays a very important role in creating a very competitive advantage for a company, because this logistics management can reduce operational costs, speed up delivery time, and can also increase customer satisfaction in the company.